Development of Multiple Myeloma of the IgA Type in a Patient with Cold Agglutinin Disease: Transformation or Coincidence? - Øystein Sefland; Ulla Randen; Sigbjørn Berentsen (Case Reports in Hematology)
Cold agglutinin disease (CAD) is an autoimmune hemolytic anemia and a distinct, clonal bone marrow lymphoproliferative disorder, characterized in most cases by a monoclonal IgMκ serum protein. We describe a CAD patient presenting with a monoclonal immunoglobulin of the IgAλ class. For years, she remained asymptomatic apart from the hemolytic anemia until eventually she developed multiple myeloma (MM) of the IgAλ phenotype. Prior to the development of MM, her hemolytic anemia responded to rituximab monotherapy. After she was diagnosed with MM, both conditions responded well to bortezomib-based therapy. We performed further investigations to determine whether her MM represented a progression/transformation of CAD or an independent disease. Flow cytometry and biopsy findings convincingly confirmed two unrelated clonal B-cell disorders. On this background, we also discuss previously published reports on cold agglutinin activity in patients with IgA gammopathy. In conclusion, cold agglutinins of the IgA class do probably not result in CAD. If a monoclonal immunoglobulin other than IgMκ is found in a patient with CAD, the coexistence of two unrelated B-cell clones should be suspected.